2015
DOI: 10.1155/2015/713218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy Observation of Acupuncture Treatment for Nonarteritic Anterior Ischemic Optic Neuropathy

Abstract: Objective. To determine whether acupuncture treatment impacts the clinical efficacy of degenerative damage of the optic nerve caused by nonarteritic anterior ischemic optic neuropathy (NAION). Methods. 69 patients (93 eyes) with NAION who had been treated by acupuncture which is performed on different acupoints related to eyes by vertical insertion or Fingernail-pressure needle insertion. The best corrected visual acuity, mean defect (MD) and mean light sensitivity (MS) of the visual field, and latency and amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Notably, one reported case series found that acupuncture, a traditional Chinese medicine, was successfully applied to treat ITON [ 46 ]. Acupuncture has also been reported to help patients with ischemic optic neuropathy [ 47 ], though it has not been shown to be successful in treating glaucoma [ 48 ]. Until other therapies are proven beneficial, it appears reasonable to consider further studying the potential of acupuncture given its very low risk.…”
Section: Treatmentmentioning
confidence: 99%
“…Notably, one reported case series found that acupuncture, a traditional Chinese medicine, was successfully applied to treat ITON [ 46 ]. Acupuncture has also been reported to help patients with ischemic optic neuropathy [ 47 ], though it has not been shown to be successful in treating glaucoma [ 48 ]. Until other therapies are proven beneficial, it appears reasonable to consider further studying the potential of acupuncture given its very low risk.…”
Section: Treatmentmentioning
confidence: 99%
“…Acupuncture has also been used for treatment of ocular diseases, including glaucoma, age-related macular degeneration (AMD), retinitis pigmentosa, etc (Jiao, 2011; Xu et al, 2012; Law and Li, 2013; Xu and Peng, 2015). In Traditional Chinese Medicine, GB20 and BL1 are the common acupoints selected for acupuncture treatment of ocular diseases (Qin et al, 2015; Xu and Peng, 2015). Although acupuncture is widely used for ocular therapy, the effect of acupuncture treatment on regulation of retinal transcriptome especially those changed by ONC injury is totally unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, as a supplementary alternative therapy, is often used for the treatment of eye disease. Studies have found that acupuncture can improve the mean light sensitivity of patients with non-arteritic anterior ischemic optic neuropathy and reduce the mean defect ( Qin et al, 2015 ), as well as improve the visual acuity and contrast sensitivity (CS) of patients with retinitis pigmentosa and nystagmus ( Bittner et al, 2014 ; Blechschmidt et al, 2017 ). Myopia is one of the common visual disorders that can lead to a loss of visual quality ( Zorena et al, 2018 ), and the global prevalence of it has been increasing in recent years; it is estimated that the myopic population will account for 49.8% of the total global population by 2050 ( Baird et al, 2020 ; Dong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%